Design of a logic and programmable controller based on the motorola microcontroller (2006)
This article, present the results archieved in the design of a PLC based on a microcontroller. using the norms of electromagnetic compatibility. A design of sofware and hardware was carried out and this design was implemented in an industrial atmosphere, obtaining very good results, in front of the electromagnetic noise characteristic of the industrial atmosphere.